Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1002/(sici)1097-0088(199804)18:5<541::aid-joc270>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

A 30-year (1964–1993) daily rainfall data base for the Spanish Mediterranean regions: first exploratory study

Abstract: A dense daily precipitation data base, extending from 1964 to 1993, has been created for the Mediterranean regions of Spain. It is composed of complete and homogeneous series at 410 raingauge stations (347 in the coastal fringe of peninsular Spain, and 63 in the Balearic Islands). The region offers an interesting scenario for mesoclimatological studies on time and spatial rainfall variability: geomorphologically, it is characterized by important coastal relief units and complex distribution of sea and land mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
148
0
8

Year Published

1999
1999
2014
2014

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 213 publications
(163 citation statements)
references
References 18 publications
7
148
0
8
Order By: Relevance
“…With regard to the European context, negative trend areas are more pronounced in the central and southern regions, corresponding to the Mediterranean basins, whose most relevant characteristic is extreme rainfall variability, both in space and time (Piervitali et al, 1997;Schonwiese and Rapp, 1997;Romero et al, 1998;Millán et al, 2005;Mehta and Yang, 2008). The implications of these changes are particularly significant for these areas, stressed by the combination of a dry climate and an excessive water demand.…”
Section: Introductionmentioning
confidence: 53%
“…With regard to the European context, negative trend areas are more pronounced in the central and southern regions, corresponding to the Mediterranean basins, whose most relevant characteristic is extreme rainfall variability, both in space and time (Piervitali et al, 1997;Schonwiese and Rapp, 1997;Romero et al, 1998;Millán et al, 2005;Mehta and Yang, 2008). The implications of these changes are particularly significant for these areas, stressed by the combination of a dry climate and an excessive water demand.…”
Section: Introductionmentioning
confidence: 53%
“…Thus, along the Mediterranean coast, during 1964-1990, Romero et al (1998 found a global decrease in winter precipitation in 410 observatories, but González-Hidalgo et al (2006) reported a significant positive trend between 1951 and 2000 in the same area. A decrease in autumn precipitation was reported in the Gulf of Valencia (on the east coast) between 1961and 1990(González-Hidalgo et al, 2001 and an increase in summer precipitation (mainly inland) was observed during 1961-1990 by Mosmann et al (2004) using 333 observatories.…”
Section: Discussionmentioning
confidence: 99%
“…The Iberian Peninsula is an interesting area for such a study because the climate regime varies from temperate-maritime (in the northwest) to Mediterranean. In particular, the southeastern region of Spain has the lowest mean annual rainfall of any European region (Rodriguez-Puebla et al, 1998;Romero et al, 1998). The peninsula is affected by both Atlantic and Mediterranean influences (Rodó et al, 1997, Esteban-Parra et al, 1998Rodriquez-Puebla et al, 1998;Romero et al, 1998;Corte-Real et al, 1999;Serrano et al, 1999;Trigo and DaCamara, 2000), including the North Atlantic oscillation (NAO) (Hurrell, 1995;Rodó et al, 1997;Esteban-Parra et al, 1998;Marshall et al, 2001).…”
Section: Aims Of the Studymentioning
confidence: 99%